ANALISA PAPAN REKLAME NAMA TOKO TERHADAP KUALITAS VISUAL DAN VISIBILITAS - Mulia , Endi Martha; Sihotang , Harlen; Wijaya, Jansen; Limada, Immanuelly Agustine Putri (LPPM ISTP, 2025)
The rapid growth of development and business in Medan City has driven the use of billboards as an effective promotional medium. In the area of Jalan Putri Hijau Merak Jingga to Jalan Perintis Kemerdekaan, store signage billboards appear densely packed and disorganized. This study aims to analyze the visual quality and visibility of billboards in that area in relation to the buildings. The research uses a qualitative method, with data collected directly on-site and analyzed using a research formula consisting of variables such as proportion and scale, color, harmony and contrast, and viewing distance. The results show that the visual quality of the billboards in this area is low and does not align with existing visual aesthetic theories for signage on buildings. However, in terms of visibility (viewing distance), the billboards are considered to comply with existing theory. This study highlights the importance of proper billboard placement aligned with visual aesthetics and functional clarity.